Speaking to the Ancestors. Religion as Interlocutory Interaction - Singleton, Michael (Anthropos, 2009)
Material from an indigenous manuscript, combined with fieldwork in Ubungu (Tanzania) and relating to what conventionally but questionably was styled "ancestor worship" could, less ethnocentrically and keeping closer to the empirical evidence, be more satisfactorily described as "speaking to the ancestors." Extrapolating from this case study, much of what still goes in Western circles, academic and otherwise, as "Primitive Religion," could be more credibly considered as interlocutory interaction.
free